Barriers and facilitators to shared decision-making in oncology: a systematic review of the literature - Covvey, Jordan R.; Kamal, Khalid M.; Gorse, Erin E.; Mehta, Zumi; Dhumal, Trupti; Heidari, Elham; Rao, Deepika; Zacker, Christopher (Supportive care in cancer, 2019)
Purpose Shared decision-making (SDM) is a strategy to facilitate patient-centered care and is increasingly important in oncology, where patients are faced with complicated treatment decisions that require them to weigh efficacy and safety, quality of life, and cost. Understanding the contributors to the use of SDM may provide insight to its further implementation. Therefore, the objective of the study was to examine the patient-related barriers/facilitators to SDM in oncology care. Methods A systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was executed. A search strategy composed of cancer, decision-making, and patient-centered terms was conducted utilizing PubMed, EBSCO MEDLINE, Scopus, CINAHL, and the Cochrane Library databases between January 2007 and November 2017. Full-text, US-based, English language articles describing the patient perspective of SDM in oncology care were included. Relevant data from articles were reviewed in a qualitative synthesis. Results From 3435 potential citations, a total of 35 articles were included. The most common cancers studied were breast ( n = 22; 62.9%) and prostate ( n = 9; 25.7%). The identified themes for barriers to SDM were uncertainty in the treatment decision, concern regarding adverse effects, and poor physician communication. Themes for facilitators for SDM included physician consideration of patient preferences, positive physician actions and behaviors, and use or encouragement of support systems. Conclusion As SDM gains use within oncology practice, understanding key influences will allow for more effective implementation of strategies to increase patient engagement and improve care and value in the treatment process.